Distributed Cooperative Voltage Control of Networked Islanded Microgrid via Proportional-Integral Observer - Yan, Shen; Gu, Zhou; Park, Ju H.; Xie, Xiangpeng; Sun, Wei (IEEE transactions on smart grid, 2024)
This article is concerned with the proportional-integral observer-based distributed cooperative voltage control issue of the networked islanded microgrid subject to probabilistic communication delay. Due to the fact that the reference signal is usually received by partial distributed generators, the system model with a constant reference signal in some existing results is difficult for control synthesis. To solve this problem, a distributed control law based on the measured voltage is designed to estimate the reference signals for all distributed generators. Then, by treating the deviation between the estimated and measured voltages as the small signal, a novel small-signal model of the networked microgrid voltage control system is established. With the utilization of the probabilistic feature of communication delay, a distribution-dependent delay handling manner is taken into account. To improve the estimation accuracy of the system state, a proportional-integral observer is adopted based on the local measured voltage. With the aid of Lyapunov theory and linear matrix inequality technology, sufficient criteria are proposed for co-designing the controller and observer gains to guarantee that the reference voltage is tracked by all distributed generators. Lastly, some simulation results are carried out to manifest the merits of the developed strategy.